EVALUATION OF REGIONAL REVENUE AND EXPENDITURE BUDGETS IN THE PALU CITY GOVERNMENT - Gollah, Shery Natalia; Paranoan, Selmita; Yamin, Nina Yusnita; Masruddin, Masruddin (Journal of Applied Accounting, 2025)
Post-calamity 2018 and the COVID-19 pandemic caused the fiscal performance of Palu City Government to change significantly. For this study, the dynamics of the 2019-2023 Palu City APBD are to be evaluated through growth and variance analysis in an attempt to provide responsive fiscal policy recommendations. Quantitative methods apply by processing the secondary data with APBD reports. Results showed an "explosion-consolidation" trend of spending and revenue variance > 100% in 2019-2022 (conservative) that declined to 96.08% in 2023, indicating the necessity to re-adjust PAD projection assumptions; spending variance increased from 57.05% to 95.26%, reflecting an increase in absorption capacity but not yet quantifiable outcome effectiveness. The trend of revenue-expenditure growth reflects an expansionary response in the crisis phase and consolidation in the recovery phase. These findings underscore the necessity to diversify PAD sources, enhance budget projection models with macro-economic drivers and contingency projections, and strengthen the absorption capacity of spending with e-budgeting and real-time monitoring as the basis for adaptive fiscal policies to improve the resilience and accountability of APBD in disaster-prone areas.